2021
DOI: 10.1088/1757-899x/1031/1/012056
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the day of storage of dairy products by data combination

Abstract: Existing methods for tracking changes in the quality of dairy products are characterized by difficulty, time consuming, a large number of calculation procedures and resources, which makes them unsuitable for “on-line” monitoring. In the present work, feature vectors containing color components, spectral indices and physicochemical parameters of the products are used. Methods for selection of informative features based on consistently improving assessments have been applied. Models by principal components and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…This improves the accuracy reported by Vasilev et al [16], where the authors indicated a maximum accuracy of 89% in predicting a day of cheese storage. In the present work, by up to 33% the accuracy of prediction of the storage day of cheese, which was reported by Vasilev et al [6], was increased who use data in the visible region of the spectrum. Added the data of Atanassova et al [2], who indicated that by means of data from NIR spectral characteristics (900 -1700 nm), in selected spectral ranges, the determination of basic technological characteristics of cheese is possible with an accuracy of 95%.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…This improves the accuracy reported by Vasilev et al [16], where the authors indicated a maximum accuracy of 89% in predicting a day of cheese storage. In the present work, by up to 33% the accuracy of prediction of the storage day of cheese, which was reported by Vasilev et al [6], was increased who use data in the visible region of the spectrum. Added the data of Atanassova et al [2], who indicated that by means of data from NIR spectral characteristics (900 -1700 nm), in selected spectral ranges, the determination of basic technological characteristics of cheese is possible with an accuracy of 95%.…”
Section: Resultssupporting
confidence: 59%
“…The mentioned authors found that the use of data in the visible range of the spectrum (380-780 nm) is not appropriate for predicting changes in the surface characteristics of cheese, especially in the early stage of the development of mold fungi. Vasilev et al [6], develop predictive models for a day of cheese storage from three Bulgarian producers. For this purpose, the authors use vectors of color components and spectral indices obtained from spectral features in the VNIR region (600-1100 nm).…”
Section: Introductionmentioning
confidence: 99%
“…When there is a need to predict the values of a grouping variable, discriminant analysis (DA) is a useful technique in multivariate data analysis [29]. This is known as classification or pattern recognition.…”
Section: Classification Methodsmentioning
confidence: 99%
“…The processing of the survey data was done with the Principal Component Analysis (PCA) method [18][19][20]. It is a multivariate statistical method used to reduce the dimensionality of a data set while retaining most of the variability present in the data.…”
Section: Data Analysis Methodsmentioning
confidence: 99%